A novel sesquiterpene and three new phenolic compounds from the rhizomes of Acorus tatarinowii Schott. Issue 19 (1st October 2015) - Liang, Shuang; Ying, Shu-Song; Wu, Hong-Hua; Liu, Yan-Ting; Dong, Peng-Zhi; Zhu, Yan; Xu, Yan-Tong
Graphical abstract: Abstract: A novel sesquiterpene with an unprecedented epoxy lactone skeleton, named tatarinolactone, together with two new amides, a new biphenylpropanoid and two known lignans were isolated from the rhizomes of Acorus tatarinowii Schott. Their structures were identified as 6, 7, 8-trihydroxy-4α-isobutyl-4, 7-dimethylhexahydro-6, 8α-epoxychromen-2(3 H )-one (1 ), ( E )-methyl 4-[3-(4-hydroxy-3-methoxyphenyl)acrylamido]butanoate (2 ), ( Z )-methyl 4-[3-(4-hydroxy-3-methoxyphenyl)acrylamido]butanoate enol isomer (3 ), ( R )-4-hydroxy-3-[1-hydroxy-3-(4-hydroxy-3-methoxyphenyl)propan-2-yl]-5-methoxybenzoic acid (4 ), (2 S, 3 R )-ceplignan (5 ), and (2 R, 3 S )-ceplignan (6 ), respectively, based on extensive spectroscopic analysis and by comparison to the known compounds. To test their effects on serotonin transporters, a high content assay using hSERT-HEK293 cell line was adopted. Results indicated that compounds1 and4 significantly inhibited SERT activity, while compounds2, 3, 5, and6 significantly enhanced SERT activity, which partly explain the traditional uses of the rhizomes of Acorus tatarinowii Schott in treatments of neuropsychiatric and digestive disorders.